A conceptual model for talik dynamics and icing formation in a river floodplain in the continuous permafrost zone at Salluit, Nunavik (Quebec), Canada - Lemieux, Jean-Michel; Fortier, Richard; Molson, John W. H.; Liu, Weibo (Permafrost and Periglacial Processes, 2021)
Icing occurs each winter along the floodplain of the Kuuguluk River in the continuous permafrost zone at Salluit in Nunavik (Quebec), Canada. The source of successive water overflows which thicken and enlarge this ice cover over time is suprapermafrost groundwater discharging from a talik below the riverbed. Electrical resistivity tomography was used to delineate the talik, while water level and temperature dataloggers were used to assess the thermo-hydraulic conditions of the riverbed. The mean annual riverbed temperature was 1.8°C in 2016 while the mean annual air temperature was −6.0°C. Hydraulic heads below the ice cover as high as 2.8 m and events of abrupt decreases in hydraulic head due to suprapermafrost groundwater overflow through cracks in the ice cover were monitored. An analytical solution based on beam mechanics theory was used to assess the water pressure-induced stresses which are sufficient to fracture the ice cover. A detailed conceptual model of the talik and icing dynamics is proposed to explain the cryo-hydrogeological processes taking place in this complex groundwater–river system. The groundwater pressure buildup in the talik during the winter is due to constricted flow of suprapermafrost groundwater in the talik. These results have implications for understanding the dynamics of river taliks and their use as potential water supplies in northern communities.